La Vita : 2-maandelijks magazine voor lesbische en biseksuele vrouwen in Noord-Nederland. (Leeuwarden : Selda, 2002)
Fonds Suzan Daniel (FSD)
Periodiciteit: tweemaandelijks
Redactie: PB 4023, 8901 EA Leeuwarden
Nederlands
Periodiek